Experimental multiaxial fatigue tests realized with newly developed geometry specimens. Issue 4 (22nd November 2018) - Morettini, Giulia; Braccesi, Claudio; Cianetti, Filippo
Abstract: In the literature there are many experimental results of multiaxial fatigue testing, usually generated by the combination of two or more cyclical loads. The cases in which samples are randomly stressed are rarer. Moreover, to generate particular stress states, the use of specific machinery for fatigue tests is usually required. For these reasons, the authors have created a particular geometry of specimens, which, when solicited by a single input of a random type, guarantees the creation of specific multiaxial stress states without using complex and costly instruments. The experimental tests were finally used for the validation of the multiaxial reduction method developed and currently utilized in the authors' design phase, though potentially used to verify all the other methodologies present in the literature.